MODEL OF THE THERMOBARIC CONDITIONS OF COAL GENERATION - Makarov D.V.; Mazor Y.R. (My University, 1988)
We attempt to define the different roles of temperature and pressure under different conditions of coal metamorphism. Specifically, we analyze the dependence of the vitrinite reflectivity on the maximum paleotemperatures and paleodepths of burial of coal seams. Our model was derived for deposits that have reached the maximum temperatures at a temperature T0 = 0 in the neutral layer. The model can be used to determine more accurately the conditions under which so-called 'postinversional' metamorphism of coal occurs. We find that at low geothermal gradients, at which coal metamorphism takes place at relatively high temperatures, the main oil generation zone will begin and end at lower temperatures, i.e., at temperatures corresponding to lower degree of coalification.